Determination of indium using vortex assisted solid phase microextraction based on oleic acid coated magnetic nanoparticles combined with slotted quartz tube-flame atomic absorption spectrometry - Celik, Birgul; Akkaya, Erhan; Bakirdere, Sezgin; Aydin, Firat (ELSEVIER SCIENCE BV, 2018)
A solid phase microextraction (SPME) method combined with slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS) was developed and optimized for the extraction and the determination of trace indium in different matrices. The method relies upon SPME that uses oleic acid coated magnetite nanoparticles (MNPs) followed by analysis with SQT mounted FAAS. After the enhancement in sensitivity by means of SPME, further improvement in sensitivity was provided by SQT which improves the detection power of conventional FAAS. The easy separation of extracted indium from the media was facilitated using an external magnetic field. Some effective parameters on the development of the method such as pH of the analyte solution, amount of eluent, amount of MNPs were optimized to obtain maximum absorbance value at each optimization step in order to achieve an improved detection power. Under the optimum experimental and instrumental conditions, the enhancement factor of 44 was obtained where the limit of detection and the limit of quantification were found to be 6.02 mu g/L and 20.06 mu g/L, respectively. Recovery tests were also studied in order to demonstrate the accuracy of the developed analytical method and satisfactory outcomes were obtained.
Keywords: Indium; Magnetic nanoparticles; Oleic acid; Slotted quartz tube; Flame atomic absorption spectroscopy; LIQUID-LIQUID MICROEXTRACTION; PLASMA-MASS SPECTROMETRY; ULTRATRACE LEVELS; TRACE AMOUNTS; ICP-MS; CADMIUM; SAMPLES; WATER; PRECONCENTRATION; EXTRACTION; Chemistry